Pusat Industri Kreatif Melalui Pendekatan Arsitek Ieoh Ming Pei - Panji Kustoro Danuarta Riady; Rina Saraswaty (Jurnal Ilmiah Teknik Sipil dan Arsitektur (JITAS), 2023)
According to the Ministry of Trade of the Republic of Indonesia (2009), the creative industry is an industry that originates from the utilization of individual creativity, skills and talents to create welfare and employment where according to the ministry of creative economy statistics there are 17 creative economy sub-sectors that are developing in Indonesia. From the data, this has enormous potential so that the economic sector in Medan city increases. Because Medan is one of the cities that has the largest population outside Java. Many creative industry players in the city of Medan operate individually. So that many products / works produced are less varied. With this problem faced, therefore the need for a place or container that can accommodate the activities of creative industry players. The place is called the Center for Creative Industries. In this